Le Fort I Approach for Midline Tumors of the Palate. Issue 4 (December 2015) - de Cevallos, Jorge Guiñales Díaz; Carretero, Jose L. Cebrián; de Vera, Jose L. Del Castillo Pardo; García, Miguel Burgueño
Midline tumors of the palate may represent a challenge for the maxillofacial surgeon. Their resection and immediate reconstruction could be hindered when a simply intraoral approach is selected. The Le Fort I downfracture approach represents an ideal technique for the management of this tumors, simplifying their resection, ensuring a tumor-free margin, and allowing their reconstruction with a temporal muscle flap. A review of this procedure is presented, highlighting the technical keys and its principal advantages.